Alpha-amylase inhibition kinetics by caulerpenyne - CENGIZ, S.; CAVAS, L.; YURDAKOC, K. (Mediterranean Marine Science, 2010)
Many algae have important secretions which are generally used for defensive purposes. These secretions take attentions of a lot of researchers who are wondering if these metabolites can be used for medical researches or not. Among these metabolites, caulerpenyne (CYN) which is the main metabolite of Caulerpa species, have had an important place in Caulerpa researches since the results related to its determined properties such as cytotoxic, antiviral, antiproliferative and apoptotic effects have been proven by many scientific reports. In the present study, the inhibitory effect of CYN isolated from C. prolifera on alpha-amylase was investigated. The inhibition experiments were done with CYN by spectrophotometric determination method. In order to evaluate the type of inhibition Lineweaver–Burk plot was produced. The results obtained from enzyme kinetic studies exhibited an un-competitive type of inhibition, which is characterized by the difference of Vmax and KM from those of the free enzyme, of alpha-amylase in the presence of CYN. The present study showed that Caulerpa species can be a potential target for producing diabetic drugs in the light of the results obtained for CYN.